Another look on product diversity: some new propositions to design profitable product ranges. (17th June 2008) - Ballot, Eric; Segrestin, Blanche; Weil, Benoit
Over the past years, automotive manufacturers have continuously renewed and expanded their product offer. Yet, despite the increasing differentiation of the offer, the sales' distribution appears to be concentrated on a limited number of versions. In these conditions, we can wonder whether diversity can effectively sustain the economic growth. What kind of diversity would support sustainable growth? The article aims at addressing this question by exploring a new hypothesis: the consumers' choice dilemma. This hypothesis makes it possible to analyse in a new way the critical role of dealers in guiding the consumers' choices and the related risks of undervaluing innovation. It then suggests alternative strategies to design diversified but profitable product ranges.